Four new megastigmane glycosides from the leaves of Eucommia ulmoides Oliver. (October 2018) - Yan, Jian-Kun; Shi, Xu-Liu; Donkor, Paul Owusu; Ding, Li-Qin; Qiu, Feng
Graphical abstract: Highlights: Four new megastigmane glycosides were isolated from the leaves of Eucommia ulmoides Oliver. The absolute configurations of all compounds were determined based on DFT calculations of OR and chemical method. All compounds were investigated their ACE inhibitory activities in vitro . Abstract: Four new megastigmane glycosides, eucomegastigsides E1 (1 ), eucomegastigsides E2 (2 ), eucomegastigsides F1 (3 ), and eucomegastigsides F2 (4 ) were isolated from the leaves of Eucommia ulmoides Oliver. Their structures were elucidated based on extensive spectroscopic analysis and their absolute configurations were determined by comparison of experimental optical rotation (OR) to DFT calculations. In addition, compounds1 -4 were evaluated for their ACE (Angiotensin Converting Enzyme) inhibitory activities using HPLC. All compounds showed moderate inhibitory effects on ACE.